Influence of translanguaging in writing across languages: A case of multilingual primary students in Sri Lanka - Nihmathulla, Mohmed Cassim Badurusaman (Journal of Modern Languages, 2024)
Studying aspects of multilingualism, such as the dynamics of multilingual and linguistic variation, is a widely documented phenomenon. What remains relatively less explored in such studies, however, concerns how translanguaging (TL) influences writing across languages. This study considers essays written by three students at the primary level of education in Sri Lanka in their first language (L1/Tamil), second language (L2/English) and third language (L3/Sinhala). The purpose of the study is to comprehend how TL practices influence their writing and to report on the reflections of the students and their teachers on TL in writing. The study provides insights into how TL supports student writing across languages and the views of teachers and students on TL in writing. Additionally, implications for the education of multilingual students are discussed.